(untitled) (Journal Of Educational and Psychological Researches, 2013)
The research aims at:- 1- Measuring the self-image of the elderly. 2- Measuring the depression of the elderly. 3- Knowing the statistically difference of the self-image to the elderly due to variables like (the gender , martial status and place of residency). 4- Knowing the statistically difference of the depression of the elderly due to (the gender , martial status and place of residency). 5- Knowing the relationship between the self-image and depression of the elderly. To reach to the aims of the research , the researcher built a tool to measure self-image and other to measure the psychological disorders for elderly , and after investigation of their validity and reliability he applied them on a random sample of elderly (their number was 225). After collecting the data and treating them statistically by using t-test for one sample and three way Anova and Pearson correlation coefficient the researcher concluded the follows :- 1- It sounds that the elderly have a positive self-image. 2- It sounds that the elderly do not suffer from depression. 3- There is statistically significant in self-image due to genders variable for males ,and martial status for married ,and residency variable for the resident in their homes , also there is interaction between gender and martial status. 4- There is statistically significant in depression due to martial status variable for the bachelors and others in comparison with the married , and residency variable, for the residents in Institutions caring, whereas there no difference in depression due to the elderly gender. 5- There is an opposionsl and strong relationship between self-image and depression .